Beyond Clicks and Likes: Unraveling the Power of Personalization, Gamification, and Influencer Marketing in Digital Consumer Engagement - Dewatmoko, Santo (Manunggal Halim Jaya, 2025)
This study explores the impact of digital consumer engagement strategies—specifically personalization, gamification, and influencer marketing—on consumer interaction and brand loyalty in the digital marketing landscape. Using a qualitative research approach, data were collected through semi-structured interviews with marketing professionals and consumers, alongside content analysis of brand-consumer interactions on social media platforms. The findings reveal that personalization enhances consumer trust and satisfaction by tailoring marketing content to individual preferences, but ethical concerns regarding data privacy must be addressed to maintain engagement. Gamification fosters intrinsic motivation and habitual brand interaction through reward-based systems and social competition, proving effective in sustaining long-term engagement. Additionally, influencer marketing significantly influences consumer perceptions and purchase intentions, particularly when micro-influencers—who are perceived as more relatable and credible—are involved in brand collaborations. However, challenges such as content saturation, privacy concerns, and diminishing engagement effectiveness over time necessitate continuous adaptation of digital marketing strategies. The study contributes to theoretical advancements in consumer engagement research while providing practical implications for marketers, emphasizing the need for dynamic, consumer-centric digital strategies that align with evolving consumer expectations in competitive online environments.